2015
DOI: 10.1016/j.sjbs.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophyte and non dermatophyte fungi in Riyadh City, Saudi Arabia

Abstract: The results concluded that approximately M. canis caused a quarter of dermatophyte cases, tinea capitis infection was prevalent and the molecular method was more accurate than conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 30 publications
9
38
1
Order By: Relevance
“…albicans as a major isolate accounting 5/13(38.4%) of the total yeast isolated and this study was similar with study conducted in Saudi Arabia [33]. Non dermatophyte fungi were isolated as a cause of dermatophytosis in many studies [9,13,33,34].…”
Section: Discussionsupporting
confidence: 88%
“…albicans as a major isolate accounting 5/13(38.4%) of the total yeast isolated and this study was similar with study conducted in Saudi Arabia [33]. Non dermatophyte fungi were isolated as a cause of dermatophytosis in many studies [9,13,33,34].…”
Section: Discussionsupporting
confidence: 88%
“…It was noticed that T. corporis constituted the highest prevalence (40%) followed by T. pedis (18%) then T. capitis and T. cruris (16 and 8%, respectively). these results disagreed with Khaled et al, (2015) who examined 112 patients and found that the T. capitis infection had the highest prevalence among the patients (22.3%) while T. barbae had the lowest. The frequency of isolation of dermatophytes from clinically suspected human patients was recorded in Table (10) and revealed that T. verrucosum was the highest isolated dermatophyte (28%) followed by E. flocosum and M. canis (16 and 14%, respectively) and lastly T. mentagrophytes and T. violoaceum (12% of each).…”
Section: Discussioncontrasting
confidence: 83%
“…The frequency of isolation of dermatophytes from clinically suspected human patients was recorded in Table (10) and revealed that T. verrucosum was the highest isolated dermatophyte (28%) followed by E. flocosum and M. canis (16 and 14%, respectively) and lastly T. mentagrophytes and T. violoaceum (12% of each). This result was found coincided with Khaled et al, (2015) who observed that the identified dermatophyte isolates were belonged to nine species as T. violaceum, T. verrucosum, T. rubrum, T. mentagrophytes, T. schoenleinii, T. concentricum, M. canis, M. audouinii and E. floccosum while it disagreed with Bhatia and Sharma, (2014) who noticed that T. mentegrophyte was the predominant spp.…”
Section: Discussionsupporting
confidence: 73%
“…In a study of human pathogenic dermatophytes, Khaled et al (2015) reported that the correlation between the type of tinea and dermatophyte species was dependent on the type of keratin. They found that Microsporum canis prefers keratin in the scalp and skin, whereas Epidermophyton floccosum prefers keratin in dead tissues (groin, feet and nails).…”
Section: Incorrect Diagnosis and Differentiation Of Dermatophytesmentioning
confidence: 99%